Characteristics of Good Governance and its Impact on Village Financial Management - Arfail, Arfail; Riyanti, Riyanti; Sultan, Sultan (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: This study aims to test and analyze the characteristics of good governance and its impact on village financial management in Sumpira village, Baebunta Selatan sub-district. Design/methodology/approach: This research uses quantitative methodology based on quantitative through distributing questionnaires. In this study the population was employees in the Sumpira village office. While the sampling technique is saturated side (census) which means that sampling utilizes the entire population. Then the data was analyzed with the SPSS 26 program. Findings: Show your finding here Accountability has a positive effect on village financial management in Sumpira Village, while transparency has a positive effect on village financial management in Sumpira Village. Research limitations/implications: The study also revealed several obstacles in the implementation of good governance, such as the lack of human resource capacity and resistance to change. Practical implications: By applying the characteristics of good governance in village financial management, it is expected that transparent, accountable, participatory, efficient, fair, responsive, consensual, and law-abiding management can be achieved. This will have a positive impact on improving the welfare of village communities and sustainable development. Originality/value: This title is not only original but also has significant potential value in various aspects both theoretical and practical. By examining the characteristics of good governance and its impact in the context of village financial management, this research can make a meaningful contribution to improving governance and welfare at the village level. Paper type: Research paper